Akten, Eingaben, Schaufenster : die DDR und ihre Texte ; Erkundungen zu Herrschaft und Alltag - Lüdtke, Alf 1943-2019 Hrsg; Becker, Peter 1962- (Akademie-Verl, 1997)
Erkundungen zu Herrschaft und Alltag